Investigational Drugs for the Treatment of Depression (Part 2): Glutamatergic, Cholinergic, Sestrin Modulators, and Other Agents - Vasiliu, Octavian (Frontiers in Pharmacology, 2022)
A large number of investigational drugs with antidepressant activity are currently explored in different phases of clinical research, with indications as major depressive disorder, treatment-resistant major depression, bipolar depression, post-partum depression, late-life depression, etc. Although the vast majority of the antidepressants in clinical use are based on the monoaminergic hypothesis of depression, recent data supported the launching on the market of two new, non-monoamine-modulating drugs. Esketamine for treatment-resistant major depression and brexanolone for post-partum depression are these two exceptions from the monoaminergic model, although their use is still limited by high costs, unique way of administration (only intravenously for brexanolone), physicians’ reluctance to prescribe new drugs, and patients’ reticence to use them. Glutamatergic neurotransmission is explored based on the positive results obtained by intranasal esketamine, with subanesthetic intravenous doses of ketamine, but also D-cycloserine, traxoprodil, MK-0657, AXS-05, AVP-786, combinations of cycloserine and lurasidone, or dextromethorphan and quinidine being explored as therapeutic options for mono- or bipolar depression. Sestrin modulators, cholinergic receptors modulators, or onabotulinumtoxinA have also been investigated for their potential antidepressant activity. In conclusion, there is hope for new treatments in uni- and bipolar depression, as it became clear, after almost 7 decades of monoamine-modulating antidepressants, that new pathogenetic pathways should be targeted to increase the response rate in this population.